Numerical Investigation and Thermal Analysis of a Refrigerant-heated Radiator Heating System coupled with Air Source Heat Pump. (February 2019) - Shao, Suola; Zhang, Huan; Jiang, Lingfei; You, Shijun; Zheng, Wandong
Abstract: A new type of refrigerant-heated radiator heating (RRH) system combined with air source heat pump (ASHP) is proposed. This system is adopted in the rural area of Tianjin because of its high efficiency and low investment cost. In this paper, a comparative study between the refrigerant-heated radiator and traditional air conditioner is carried out. The results show that the temperature distribution of the RRH system heating room in the vertical direction is more reasonable, which is less than 3 °C at the condensation temperature of 41 °C. Compared with the air conditioner heating (ACH) system, the energy utilization efficiency of the RRH system is much higher. Furthermore, the indoor thermal comfort of the RRH system is also analyzed, as well as the coupling relationship between the radiator surface and the ASHP condensing temperature. This RRH system has the prospect to be popularized in the coal-to-electricity conversion project of northern rural areas and provides a feasible solution for the winter heating problem in the non-heating areas of China.